Keabsahan Kontrak Secara Elektronik Sebagai Alat Pembuktian Di Tinjau secara Hukum Perdata - Ni Luh Putu Sudarini; dewa gede pradnyana yustiawan (Jurnal Hukum dan Sosial Politik, 2023)
Decision of the Constitutional Court Number 20/PUU-XIV/2016 states a lawsuit if civil procedural law applies to evidence. This is because there are differences in the law of proof with civil and criminal procedural law and considering the validity of evidence as a matter of procedural law also affects the legality of making documents, especially with electronic documents. Based on this description, the researcher makes several notes, especially regarding the certainty of an electronic contract law in Indonesia and the legality of e-contracts as evidence from a civil law point of view. The research results form the basis of legal certainty for electronic contracts in Indonesia based on article 5 of Law No. November 2008 concerning information and electronic transactions stipulated by the Constitutional Court Decision No. 20/PUU-XIV/2016, still based on the legality of electronic contracts used as evidence from a civil law perspective sourced from the decision of the Constitutional Court 20/PUU-XIV/2016 and provisions related to contracts in general are contained in the Civil Code.